Penafsiran Amanah Dalam Kitab Tafsir Al-Munir Oleh M. Wahbah Az-Zuhaili: (Study of the Quran Surah al-Ahzab: 72, Surah an-Nisa ': 58 and Surah al-Anfal: 27) - Sulastri, Sulastri; Rosyidah, Ainur (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2020)
The study of the interpretation of the verses of the mandate has long been discussed in the history of human life to the present day. The problem at this time is the narrow meaning of trust, so that many people are judged to have the ability to carry out the mandate, but with this ability, many actually abuse the mandate. Therefore, it is very important to review the interpretation of the verses of the mandate so that they are not understood narrowly by the community. Based on the above background, the problems raised in this paper are: 1) How are the verses of trust in the Qur'an, 2) How is Wahbah az-Zuhaili's interpretation of the mandate in the Qur'an surah al-Ahzab ; 72, surah an-Nisa'; 58 and surah al-Anfal; 27 Study of al-Munir's interpretation. This study aims: 1. to explain the verses of trust in the Qur'an, 2. Explaining the interpretation of the verses of the mandate in the interpretation of al-Munir surah al-Ahzab; 72, surah an-Nisa'; 58 and surah al-Anfal; 27 The type of research used is bibliographic in nature by using the description-analysis method, namely analysis to the primary data source of the book of Tafsir al-Munir by Wahbah az-Zuhaili. Amanah in the perspective of the Qur'an is a duty that must be carried out because it is an order from Allah SWT and Rasulullah SAW. In general, trust has a very broad and deep meaning, both in religious, economic and social aspects. While the mandate according to the book of Tafsir Al-Munir by Wahbah Az-Zuhaili is 1. Qs al-Ahzab; 72 that the mandate in question is something that is imposed on humans which contains orders and prohibitions where the burden is very large and heavy so that only humans who are willing to take it. 2. An-Nisa'58 the mandate referred to in this letter relates to many things, one of which is fair treatment. Fair to all creatures, both to groups, Muslims and non-Muslims. 3. While in Qs. Al-Anfal; 27 relating to the prohibition for believers to betray Allah, the Apostle and betray their fellow human beings as well as the recommendation to be able to maintain the trust. The mandate in question is the mandate of God and His Messenger in the form of religious rules and teachings that must be implemented, and human trust in the form of something, material or non-material that is entrusted by one person to another with a specific purpose in accordance with religious teachings.